A coupled hydraulic and mechanical system simulation for hydraulic excavators. (April 2020) - Park, Cheol-Gyu; Yoo, Seungjin; Ahn, Hyeonsik; Kim, Jooho; Shin, Daeyoung
The hydraulic system of an excavator consists of a central hydraulic power source and multiple actuator circuits. The numerical stiffness of the hydraulic system model, the complex hydraulic circuits of the excavator, and the coupling of the dynamics associated with the hydraulic system and mechanical manipulator have been major barriers to developing a real-time simulation. This article presents a coupled dynamic model of a large-sized excavator and a real-time simulation environment. A modeling approach for simulation speed while maintaining the essential features of the hydraulic system is described. The hydraulic circuit models are coded using the MathWorks Simscape Language that gives flexibilities for modeling and modularization. To make the simulation real-time capable and accurate, the entire model is divided into multiple sub-models for parallel execution, a local stiff integration solver is applied to the hydraulic sub-models, and a deliberately devised execution order is assigned to the groups of sub-models. The simulation results show good correspondence with the test results.